A CLINICO-STATISTICAL STUDY OF 40 CASES WITH PEDIATRIC MAXILLOFACIAL FRACTURES - KAMIFUSA, Takehiro; SAKUDA, Masayoshi; MATSUMOTO, Riki; NUKATA, Junichiro; FUJISHIRO, Hiromi; JOTOKU, Yoshiyuki; KANO, Yasuyuki; ADACHI, Minoru; OTA, Yoshiyuki (Pediatric Oral and Maxillofacial Surgery, 1995)
Forty cases of pediatric maxillofacial fractures, except for alveolar fractures, in children under the age of 16 years treated from January 1986 to December 1991 in our department were reviewed and analysed. Their characteristic features were as follows. 1. There were 27 boys and 13 girls and the ratio of boy to girl was 2.1: 1. By age distribution, the highest occurence was in the 13-16 age group. 2. The majority of patients (70%) visited our department within 3 days after injuries and the most (87%) came by reference. 3. The causes of maxillofacial fractures were traffic accidents (50%), falls (25%) and blows (15%). The most cases of the traffic accident were found in the 13-16 age group. 4. The frequency in occurrense of the maxillofacial fractures according to the location was 77.5% in mandible, 15% in maxilla, and 7.5% in both maxilla and mandible. The most common locations of mandibular fractures were condyle (45%), symphysis (34%) and angle (13%). The most frequent locations in children less than 4 years were symphysis and in children more than 4 years were condyle. 5. As for the time of injuries, many cases occured on Sunday and/or Thursday and in June. On the contrary, the fewest cases occured on Wensday and in February. The time zone concentrated from 12 to 16 o'clock. 6. Open reduction was performed on 15 cases (37.5%) of maxillofacial fractures. The most common osteosynthesis consisted of mini-plate (47%) and circumference wiring (33%). Thirteen cases (52%) in a conservative procedure were treated with maxillo-mandibular fixations. In the most cases of the middle third facial fractures, clinical courses were followed up. 7. Therapeutic results in all cases were found to be successful.